The challenges of studying 4chan and the Alt-Right: 'Come on in the water's fine'. (January 2022) - Colley, Thomas; Moore, Martin
In 2019, the authors led a workshop at King's College London examining how to study 4chan and assess their association with the Alt-Right. Unbeknownst to the authors, a participant was a 4chan user and started a mid-workshop thread on its notorious /pol/ (politically incorrect) board. It gained significant attention. Reviewing it later, the authors realised that this parallel thread illustrates perfectly the challenges researching 4chan – and similar – communities. We conducted discourse analysis on this unique dataset, providing an alternative perspective to predominant anthropological and informatic approaches. Our analysis enhances understanding of 'free-extremist' communities such as 4chan in several ways. It assesses how the /pol/ community responds to observation and provides new insights into roles influencers might have in radicalising others. It illustrates the value of discourse analysis in evaluating users' associations with the Alt-Right. Finally, it proposes ways researchers can overcome the challenges faced when analysing such communities.